Os sapatos lobeiros-baleeiros: práticas de calçar do século xix nas ilhas Shetland do Sul (Antártica) - Gerusa de Alkmim Radicchi (2015)
This research discusses the practice of footwear of the whalers who were in the South Shetland Islands (the maritime Antarctica) in the nineteenth century as a way of deepening the understanding of their corporeality. Will examine three groups of materiality related to wear: the body, the footwear itself and Antarctica as a place experienced, where discussed in the dialogue established with the socio-historical and cultural influences.